RESEARCH WORK AT THE UNIVERSITY OF ILLINOIS. - Littleton, A. C. (The Accounting Review, 1926)
Abstract The teachers of accounting as a group have made the major contribution, to the subject in the last thirty years. Yet, in spite of this, the technique of imparting a knowledge of accounting principles and practices, has been given very little constructive thought. Experts in educational psychology have been able to accomplish wonders in primary education by studying the technique of learning by children and of teaching for children. Certainly research might well be made in analyzing the ways of criminals and the methods under which they have operated in the past, as well as methods for preservation and especially methods of detection. Method of interpretation research in developing the best methods for presenting accounting data - the development of non-traditional statement forms, the application of graphics to accounting, the art of simplifying the essentials for report presentation and so on. The public accountant naturally enough perhaps gives so large a portion of his time to the balance sheet and other statements as of a given moment of time or at best for the fiscal period, that he has not had much opportunity to give thought to the methods of analyzing accounting data over a considerable period.